Symbolism in Sherwood Anderson's Hands , James Joice's Clay, and Ernest Hemingway's Cat In The Rain - Rahayu, Anik Cahyaning; Garnida, Susie Chrismalia; Sudarwati, Sudarwati (Universitas 17 Agustus 1945 Surabaya, 2025)
Symbolism, as a key literary device, allows authors to convey deeper meanings through objects, characters, and events, enriching the narrative and engaging readers on an emotional and intellectual level. This article explores the use of symbolism in three modernist short stories: Sherwood Anderson’s “Hands”, James Joyce’s “Clay”, and Ernest Hemingway’s “Cat in the Rain”. The research employs a qualitative descriptive design with a focus on textual analysis. The analysis is guided by theories of symbolism, psychoanalysis, and postcolonial criticism, supported by scholarly sources. Through close reading and thematic categorization, the study identifies symbols found in three short stories. Hands’ symbolisms are emotional expression, social misunderstanding and condemnation, and connection and isolation. Clay has the symbolisms of death and stagnation, disappointment and invisibility, and forgotten dreams. Cat in the Rain, on the other hand, contains symbolisms such as unfulfilled desire and emotional need, confinement and disconnection, and femininity and identity. The findings of this study show that symbolism in the three short stories not only functions as an aesthetic element, but also as a means to reveal the characters' inner conflicts and subtle social criticism. The symbols enrich the reader's understanding of the themes of loneliness, identity search, and social injustice at the core of modernist narratives. In conclusion, the use of symbolism in these works is effective in conveying complex messages that transcend the boundaries of the text, and demonstrates how modernist literature responds to social change and individual psychological conditions in a profound and meaningful way.